2018
DOI: 10.1021/acs.chemmater.7b04782
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Electrode–Electrolyte Interface of LiNi0.8Co0.15Al0.05O2 Electrodes Due to Electrochemical and Thermal Stress

Abstract: For layered oxide cathodes, impedance growth and capacity fade related to reactions at the cathode-electrolyte interface (CEI) are particularly prevalent at high voltage and high temperatures. At a minimum, the CEI layer consists of Li2CO3, LiF, reduced (relative to the bulk) metal-ion species, and salt decomposition species but conflicting reports exist regarding their progression during (dis)charging. Utilizing transport measurements in combination with x-ray and nuclear magnetic resonance spectroscopy techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 47 publications
7
60
0
Order By: Relevance
“…The peaks at 531.2 and 532.2 eV correspond to P═O (Li x PO y and Li x PO y F z ) and C═O (ROLi and LiO—C═O), respectively. In addition, the peaks at ≈533.2 eV belong to C—O—C (ether) and C—OH (alcohol), while the peaks at 534 eV are assigned to C—O (C—O—C═O, C—O—C[═O]O, O—P—F, and P—O—P═O) . However, after cycling at 4.25 and 4.45 V, the intensity of the peaks at ≈531.2 eV (P═O) is enhanced due to TMSPi decomposition.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks at 531.2 and 532.2 eV correspond to P═O (Li x PO y and Li x PO y F z ) and C═O (ROLi and LiO—C═O), respectively. In addition, the peaks at ≈533.2 eV belong to C—O—C (ether) and C—OH (alcohol), while the peaks at 534 eV are assigned to C—O (C—O—C═O, C—O—C[═O]O, O—P—F, and P—O—P═O) . However, after cycling at 4.25 and 4.45 V, the intensity of the peaks at ≈531.2 eV (P═O) is enhanced due to TMSPi decomposition.…”
Section: Resultsmentioning
confidence: 99%
“…The decompositions of the electrolyte solvent were accompanied by the gas generation such as CO 2 , CO, and C x H y . Furthermore, it has been reported that the decompositions of the solvent were enhanced with increasing the temperature . Shikano et al.…”
Section: Surface and Interfacial Chemistrymentioning
confidence: 99%
“…Recently, Lebens‐Higgins et al. demonstrated that the decomposition of the LiPF 6 salt exhibited strong correlation with the battery operation temperature . They found that the by‐products formed by the LiPF 6 breakdown existed at the room temperature above 4.25 V, however, the thermal aggravation strongly promoted the salt decompositions at the lower voltage.…”
Section: Surface and Interfacial Chemistrymentioning
confidence: 99%
See 2 more Smart Citations